1981
DOI: 10.1093/clinchem/27.11.1899
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-chromatographic determination of guanidino compounds in plasma and erythrocyte of normal persons and uremic patients.

Abstract: We describe a method for determination of guanidino compounds in plasma and erythrocytes. The compounds are separated by liquid chromatography, the concentrations in the effluent being estimated fluorometrically (Trans. Am. Soc. Artif. Intern. Organs 24: 61, 1978). Guanidinoacetic acid, guanidinosuccinic acid, guanidinobutyric acid, guanidine, methylguanidine, taurocyamine, and arginine can be detected and quantitated in both plasma and erythrocytes from healthy individuals. The method was also applied to pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 0 publications
2
10
1
Order By: Relevance
“…The ability of guanidine and its analogues to scavenge free radicals and metabolites may have significant implications in the pathogenesis of certain diseases such as uraemia and chronic renal failure. These pathological conditions are generally characterized by reduced urine production, decreased excretion of methylguanidine and guanidine (Orita et al , 1978), their accumulation in both plasma and tissues of patients (Orita et al , 1981; Kikuchi et al , 1981) and peroxynitrite production (Fukuyama et al , 1997). Although methylguanidine and guanidine produced marked inhibition at concentrations more than 100 μM in all the present experiments and these concentrations are higher than levels measured in the plasma of patients with chronic renal failure (3 μM for guanidine and 27 μM for methylguanidine) (Kikuchi et al , 1981; Orita et al , 1981), it should be pointed out that guanidine and methylguanidine can accumulate intracellularly at concentrations to 5 to 7 times higher than in plasma (Orita et al , 1981) and furthermore, they can act synergistically with other compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of guanidine and its analogues to scavenge free radicals and metabolites may have significant implications in the pathogenesis of certain diseases such as uraemia and chronic renal failure. These pathological conditions are generally characterized by reduced urine production, decreased excretion of methylguanidine and guanidine (Orita et al , 1978), their accumulation in both plasma and tissues of patients (Orita et al , 1981; Kikuchi et al , 1981) and peroxynitrite production (Fukuyama et al , 1997). Although methylguanidine and guanidine produced marked inhibition at concentrations more than 100 μM in all the present experiments and these concentrations are higher than levels measured in the plasma of patients with chronic renal failure (3 μM for guanidine and 27 μM for methylguanidine) (Kikuchi et al , 1981; Orita et al , 1981), it should be pointed out that guanidine and methylguanidine can accumulate intracellularly at concentrations to 5 to 7 times higher than in plasma (Orita et al , 1981) and furthermore, they can act synergistically with other compounds.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the serum and tissue concentrations as well as the urinary excretion rates of the potential Crn degradation products are concerned, they consistently indicate that the production of MG and creatol is increased in uremia (for references, see Refs. 21,168,169,396,479,554,598,687,722,747,1143). In CRF rats relative to controls, the concentration of MG was increased 3-to 18-fold in serum, blood cells, liver, muscle, colon, and kidney (735; see also Ref.…”
Section: H Creatin(in)e Metabolism and Renal Diseasementioning
confidence: 98%
“…Furthermore, it is noteworthy that MG can accumulate intracellularly, resulting in intracellular concentrations which are 5 to 7 times higher than the ones reported in the plasma (Matsumoto et al, 1976;Orita et al, 1981;Yokozawa et al, 1989). Indeed, MG easily accumulates in cells and in tissues, such as erythrocytes, liver, kidney and muscle, either because of the basic characteristic of molecule and/or the systemic acidosis which occurs in this disease (Kikuchi et al, 1981;Yokozawa et al, 1990). At the moment, it is uncertain to what extent MG accumulates in endothelial cells, but here we have shown that MG, acting as an inhibitor of NO-synthase, could be considered as an uraemic toxin.…”
Section: Discussionmentioning
confidence: 76%
“…Some investigators questioned the different levels of MG that have been found citing methodological difficulties, including the production of MG during assay procedure (Orita et al, 1981). Furthermore, it is noteworthy that MG can accumulate intracellularly, resulting in intracellular concentrations which are 5 to 7 times higher than the ones reported in the plasma (Matsumoto et al, 1976;Orita et al, 1981;Yokozawa et al, 1989). Indeed, MG easily accumulates in cells and in tissues, such as erythrocytes, liver, kidney and muscle, either because of the basic characteristic of molecule and/or the systemic acidosis which occurs in this disease (Kikuchi et al, 1981;Yokozawa et al, 1990).…”
Section: Discussionmentioning
confidence: 99%